2013
DOI: 10.1371/journal.pone.0060633
|View full text |Cite
|
Sign up to set email alerts
|

Sterile Alpha Motif Containing 7 (Samd7) Is a Novel Crx-Regulated Transcriptional Repressor in the Retina

Abstract: Inherited retinal diseases are mainly caused by mutations in genes that are highly expressed in photoreceptors of the retina. The majority of these genes is under the control of the transcription factor Cone rod homeobox (Crx), that acts as a master transcription factor in photoreceptors. Using a genome-wide chromatin immunoprecipitation dataset that highlights all potential in vivo targets of Crx, we have identified a novel sterile alpha motif (SAM) domain containing protein, Samd7. mRNA Expression of Samd7 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 39 publications
1
26
1
Order By: Relevance
“…Samd7 expression levels were confirmed by Northern blot analysis. Consistent with the results of in situ hybridization and the previous RT-qPCR study (37), we observed that the Samd7 expression level in the retina peaked between P6 and P14 ( Fig. S1A).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Samd7 expression levels were confirmed by Northern blot analysis. Consistent with the results of in situ hybridization and the previous RT-qPCR study (37), we observed that the Samd7 expression level in the retina peaked between P6 and P14 ( Fig. S1A).…”
Section: Resultssupporting
confidence: 92%
“…Samd7 (4930597A01Rik) was first reported to be expressed predominantly in the photoreceptor layer of the developing retina (36). Although Samd7 was shown to suppress the Crx-mediated transactivation of Retinoschisin and Samd7 promoters in a reporter assay (37), neither the molecular machinery of transcriptional suppression by Samd7 nor its in vivo function in the retina have yet been reported. Samd7 and Samd11 proteins contain a single SAM domain bearing high similarities to those of Polyhomeotic homologs (Phc).…”
Section: Significancementioning
confidence: 99%
“…Measurements were performed in duplicates. Results were analyzed with an ABI sequence detector software version 2.3 using the ΔΔCt method for relative quantification and ATP5B as stable reference gene [24]. A Ct (cycle threshold) value of 35 was used as a cutoff for estimating significantly expressed transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…Human and mouse retinal sections were used for immunofluorescence analysis, which was performed as previously described 22 (see Supplementary Text S1 online).…”
Section: Molecular Characterization Of Grid2 Deletionmentioning
confidence: 99%